Evaluation of the Antimicrobial Activity of Endophytic Bacterial Populations From Chinese Traditional Medicinal Plant Licorice and Characterization of the Bioactive Secondary Metabolites Produced by Bacillus atrophaeus Against Verticillium dahliae - Mohamad, Osama A. A.; Li, Li; Ma, Jin-Biao; Hatab, Shaimaa; Xu, Lin; Guo, Jian-Wei; Rasulov, Bakhtiyor A.; Liu, Yong-Hong; Hedlund, Brian P.; Li, Wen-Jun (Frontiers in Microbiology, 2018)
Endophytic bacteria associated with medicinal plants possess unique strategies that enhance growth and suvival of host plants, many of which are mediated by distinctive secondary metabolites. These bacteria and their secondary metabolites are important subjects for both basic and applied research aimed at sustainable agriculture. In the present study, 114 endophytic strains isolated from the wild ethnomedicinal plant Glycyrrhiza uralensis (licorice) were screened for their in vitro antimicrobial activities against common fungal pathogens of tomato (Fusarium oxysporum f. sp., Fulvia fulva, Alternaria solani), cotton (Fusarium oxysporum f. sp. Vesinfectum, Verticillium dahliae), pomegranite (Ceratocystis fimbriata), Cymbidinium (Colletotrichum gloeosporioides), and Tsao-ko (Pestalotiopsis microspora and Fusarium graminearum) and the common bacteria Staphylococcus aureus, Bacillus cereus, Salmonella enteritidis, and Escherichia coli. Several Bacillus strains, particularly Bacillus atrophaeus and Bacillus mojavensis, had a broad spectrum of antifungal and antibacterial activity. 16 strains, selected based on broad antimicrobial activity, were shown to contain at least one putative secondary metabolite-encoding gene (i.e., polyketide synthase or non-ribosomal peptide synthetase) and/or one lytic enzyme (i.e., protease, cellulase, lipase, chitinase), which may be important mediators of antagonistic activity against pathogens. Five strains, representing Bacillus atrophaeus and Bacillus mojavensis, were selected for plant growth chamber experiments based on strong in vitro antifungal activities. All five strains significantly reduced disease severity Arabidopsis thaliana plants challenged with V. dahlia infection. GC-MS analysis of cell-free extracts of Bacillus atrophaeus strain XEGI50 showed that at least 13 compounds were produced only during co-cultivation with V. dahlia, including putative compounds known to have antimicrobial activity, such as 1,2-benzenedicarboxylic acid, bis (2-methylpropyl) ester; 9,12-octadecadienoic acid (Z,Z)-, methyl ester; 9-octadecenoic acid, methyl ester, (E)-; and decanedioic acid, bis(2-ethylhexyl) ester. To our knowledge, this study is the ﬁrst to report that bacteria isolated from G. uralensis have biocontrol abilities. Our findings provide new insights into the antimicrobial activities of natural endophytes, particularly B. atrophaeus, and suggest this species may a promising candidate as a biofertilizer to confer resistance to Verticillium wilt disease and other phytopathogens in cotton and other crops.